1999
DOI: 10.1046/j.1365-2141.1999.01440.x
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid antigen co‐expression in childhood acute lymphoblastic leukaemia: relationship with in vitro drug resistance

Abstract: Contradictory data have been reported about the prognostic value of myeloid antigen co‐expression (My+) in childhood acute lymphoblastic leukaemia (ALL). In the present study the methyl thiazol tetrazoliumbromide (MTT) assay was used to compare the in vitro cytotoxicity of 14 drugs between 60 My+ (CD13+ and/or CD33+) and 107 My− ALL children at initial diagnosis. P‐glycoprotein (P‐gp), multidrug resistance‐associated protein (MRP), major vault protein/lung resistance protein (LRP) and the intracellular daunoru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 39 publications
(63 reference statements)
2
6
1
Order By: Relevance
“…The ALL patients analyzed here were classified as having myeloid antigen coexpression according to the expression of at least one of these 4 markers: CD13, CD33, CD117, and cMPO. The 25% incidence of myeloid antigen expression in this Indonesian population was slightly higher compared to what was found in Malaysia by Ng et al (2000), who reported 23% [15], but lower compared to Den Boer et al (1999) who found 36% in a European population [9] (Table 1). The variation of those findings may be due to variations in definition; some authors define myeloid positive as two or more myeloid antigens positive, or 1 or more as in this study.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The ALL patients analyzed here were classified as having myeloid antigen coexpression according to the expression of at least one of these 4 markers: CD13, CD33, CD117, and cMPO. The 25% incidence of myeloid antigen expression in this Indonesian population was slightly higher compared to what was found in Malaysia by Ng et al (2000), who reported 23% [15], but lower compared to Den Boer et al (1999) who found 36% in a European population [9] (Table 1). The variation of those findings may be due to variations in definition; some authors define myeloid positive as two or more myeloid antigens positive, or 1 or more as in this study.…”
Section: Discussioncontrasting
confidence: 57%
“…The variation of those findings may be due to variations in definition; some authors define myeloid positive as two or more myeloid antigens positive, or 1 or more as in this study. In addition, there is variation in the number of monoclonal antibodies used and which varies from only 2 monoclonal antibodies [5, 9, 15] to as many as 6 [8, 11, 12]. Besides these more technical explanations, the myeloid antigen expression may also differ due to ethnical differences.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that a single multidrug resistance transport protein (ABCC1) can be selectively up-regulated by VCR, which has been previously shown for ABCB1 in other tumor models. [23]…”
Section: Resultsmentioning
confidence: 99%
“…Expression of myeloid associated markers in ALL is well known, but its clinical significance is controversial. The reported incidence of adult ALL showing myeloid antigen expression (My+ ALL) ranges from 15% to 50%, while it varies from 4% to 35% in children (23–26). This broad variation may be related to the number of myeloid antigens studied and their degree of lineage specificity, the sensitivity of the MoAb used, the cut‐off level and technical factors (e.g.…”
Section: Immunophenotypementioning
confidence: 99%
“…The most frequently expressed myeloid antigens are CD33 (~25%) and CD13 (~23%); CD15 and CD14 can be found in ~16% of ALL cases, while CD11c is rarely present on ALL blasts (23, 27–29). Some studies have shown that the expression of myeloid‐associated antigens is a predictor of poor outcome both in childhood and adult ALL, while other studies have not confirmed this observation (24–26, 30–34). The presence of these myeloid antigens can be useful in the immunologic monitoring of MRD.…”
Section: Immunophenotypementioning
confidence: 99%